Preparation method of silicon dioxide powder and manufacturing method of quartz glass and quartz crucible containing silicon dioxide powder

By controlling the zirconia content, the synthetic silica powder is solved, and the high cost of natural quartz glass is consumed and synthesized quartz glass is high in dry etching, and efficient fluorine-resistant plasma and barium resistance are achieved, which improves the quartz crucible Performance and production efficiency of semiconductor and solar cell components.

CN119263287APending Publication Date: 2025-01-07QUZHOU NABEIXIAO QUARTZ TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411438228.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, natural quartz glass is easily consumed during dry etching, synthetic quartz glass has weak resistance to fluorine plasma and is costly, and the natural quartz powder mines used in quartz crucibles for solar cells are limited in reserves and of different quality. , the existing synthetic silica powder cannot effectively solve the problem of barium resistance.

Method used

Sodium silicate is produced using zirconium-containing compounds, heated and dissolved under a high-pressure enclosed environment, and then filtration is made of gel-calcined with hydrogen cation exchange resin to prepare synthetic silica powder containing 10-50ppm zirconia for preparation Transparent synthetic quartz glass and quartz crucibles, control zirconium oxide content to improve fluorine plasma resistance and barium resistance.

Benefits of technology

The low zirconia content of synthetic quartz glass and quartz crucibles is achieved, which improves fluorine plasma resistance and barium resistance, reduces the cost, and reduces the possibility of impurities being mixed into silicon single crystals, and improves the semiconductor and solar cell components. Production efficiency and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005085665550000081
    Figure BDA0005085665550000081
  • Figure BDA0005085665550000092
    Figure BDA0005085665550000092
Patent Text Reader

Abstract

The invention relates to a preparation method of silicon dioxide powder and a manufacturing method of quartz glass and a quartz crucible containing the silicon dioxide powder. When the sodium silicate sheet is prepared, zirconium is contained, synthetic silicon dioxide powder is prepared through an ion exchange method, and the synthetic silicon dioxide powder is prepared into a synthetic quartz crucible through arc discharge. When the synthetic quartz crucible containing zirconium oxide is used in semiconductor silicon single crystal pulling, the pulling yield of the synthetic quartz crucible is the same as that of the synthetic quartz crucible, and the purity of a cast ingot is the same as that of the synthetic quartz crucible. In addition, even when the crucible is used in solar silicon single crystal pulling, the barium resistance is greatly improved, and the single crystal yield is the same as that of a natural quartz crucible. In addition, the purity of the spindle is improved; when a sodium silicate sheet is prepared, 10-20 ppm of zirconium is doped. The synthetic silica powder is prepared by an ion exchange method, and is sintered to prepare the synthetic quartz glass containing zirconium oxide. According to the method, zirconium oxide is uniformly distributed in the synthetic quartz glass, so that the etching rate of fluorine plasma can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing silicon dioxide powder and a method for manufacturing quartz glass and a quartz crucible containing the silicon dioxide powder, and relates to the field of semiconductor manufacturing equipment. Background Art

[0002] Quartz glass composed of silicon dioxide powder has multiple usage requirements in the manufacturing process of semiconductor devices.

[0003] Among them, first, in order to manufacture semiconductor elements, it is necessary to repeatedly use manufacturing devices such as cleaning, heat treatment, photolithography, dry etching, ion implantation, CVD, and sputtering to manufacture. Quartz glass has high purity and is easy to process, and is often used in these devices. However, since the dry etching device uses fluorine plasma, the quartz glass parts are easily consumed. At present, natural quartz glass is used as dry etching parts with a line width greater than 10nm, but since natural quartz glass is made by melting natural quartz sand, there are impurities that are difficult to melt locally. For example, aluminum or zirconium. These impurities are not easily corroded by fluorine plasma, and natural quartz glass is unevenly etched, producing large particles. Since the yield of semiconductor elements is reduced by particles, it is necessary to stop the device frequently and clean it. The device needs to be conditioned for a long time before it stabilizes. The productivity of semiconductor elements decreases and the cost increases. When the line width is less than 10nm, synthetic quartz glass is used in dry etching. Since synthetic quartz glass is made of silicon tetrachloride, there are very few impurities, so there is little dust as large as natural quartz glass. Since small particles can be removed from the device by the vacuum system, cleaning when particles are generated can be greatly reduced.

[0004] The dry etching process in semiconductor device manufacturing has shifted to high-density plasma to improve productivity and quality, and components with higher purity and resistance to fluorine-based plasma are required. Synthetic quartz glass components are made of silicon tetrachloride, so they are high in purity. However, they are weak in resistance to fluorine plasma and are easily consumed. In addition, synthetic quartz glass also has the problem of high price.

[0005] Second, the quartz crucible used for pulling silicon single crystals for solar cells uses different natural quartz powders in the inner layer, middle layer, and outer layer. The inner layer uses natural quartz powder purified from American granite. The middle and outer layers are refined using Weixing granite from India. This is because of cost and the fact that natural quartz particles from purified granite have fewer inclusions. The difference in raw materials for quartz crucibles for semiconductors and solar cells is due to the use of barium in pulling single crystal silicon for solar cells. Barium converts the surface of the quartz crucible into β-quartz, which prevents peeling from the surface of the quartz crucible. Here, if synthetic silica powder is used in the inner layer, the synthetic quartz glass reacts excessively with the barium, forming a thick layer of β-quartz and peeling off.

[0006] The raw material powder used in the quartz crucible used in the silicon single crystal for solar cells is found in the mining area, mined, and refined, but the reserves of natural mines are limited, and the uneven quality has become a big problem. If it is made into synthetic silica powder, such problems can be solved, but the manufacturing cost caused by the need for barium resistance has become a problem and cannot be put into practical use. The current attempt is. When making synthetic silica powder from organosilane, aluminum is tried to be doped, but the doped aluminum is different from natural quartz and cannot enter the silica network to form mullite. Aluminum and mullite promote the quartzization of quartz glass. In addition, when aluminum is used in the inner layer of the quartz crucible, it is dissolved in the silicon melt together with the quartz glass. The segregation coefficient of aluminum is 2.00E-03, so it is easy to mix into the silicon single crystal. Aluminum acts as an N-type doping material, so it is not preferred.

[0007] In the prior art [Patent Document 1] and [Patent Document 2], a method for producing high-purity synthetic quartz powder is disclosed. The high-purity synthetic quartz powder uses low-priced water glass as a raw material, and can obtain high-purity synthetic quartz powder with a very low titanium content. The patent states that it is produced through the next process. The first process is to dealkalize the water glass to obtain a silica aqueous solution, the second process is to add an oxidant and an acid to the silica aqueous solution obtained in the first process, and then pass it through a hydrogen-type cation exchange resin, the third process is to gel the silica aqueous solution obtained in the second process to obtain silica particles, the fourth process is to wash the gelled silica, and the fifth process is to sinter the washed silica. However, there is no description of the zirconium oxide content of the produced synthetic silica powder.

[0008] Prior art literature

[0009] [Patent Document 1] CN1413169

[0010] [Patent Document 2] CN1541194 Summary of the invention

[0011] The technical problem to be solved by the present invention is to overcome the technical problems in the prior art and provide a method for preparing silicon dioxide powder and a method for preparing quartz glass and a quartz crucible containing the silicon dioxide powder.

[0012] The technical solution adopted by the present invention to solve its technical problem is:

[0013] A method for producing silicon dioxide powder comprises the following steps:

[0014] S1, using a zirconium-containing compound as an insulating material for a melting furnace for producing sodium silicate, and producing sodium silicate containing 10 to 50 ppm of zirconium oxide by contacting the insulating material with a sodium silicate melt;

[0015] S2, heating and dissolving sodium silicate containing 10-50 ppm zirconium oxide in water under high pressure and closed environment, filtering, using hydrogen type cation exchange resin to produce colloidal silicon dioxide, gelling and sintering, to produce synthetic silicon dioxide powder containing 10-50 ppm zirconium oxide.

[0016] As a further improvement of the present invention, the zirconium-containing compound is zirconium oxide or zirconium silicate.

[0017] As a further improvement of the present invention, the high-pressure closed environment is achieved by an autoclave.

[0018] A method for producing quartz glass comprises sintering the aforementioned silicon dioxide powder to make it transparent, thereby producing synthetic quartz glass containing zirconium oxide.

[0019] A method for making a quartz crucible comprises melting the silicon dioxide powder by arc discharge to make a synthetic quartz crucible containing zirconium oxide.

[0020] The beneficial effects of the present invention are:

[0021] 1. The manufacturing methods of [Patent Document 1] and [Patent Document 2] were studied, and it was found that only zirconium oxide cannot be removed in this process, so as long as the zirconium oxide content in the silicate alkali is controlled, a synthetic silica powder with a desired zirconium oxide content can be produced. In addition, the zirconium oxide content of the synthetic quartz glass after sintering and transparentizing the synthetic silica powder is also the same concentration, and even if the zirconium oxide content is a low concentration of 10 to 50 ppm, the fluorine plasma resistance becomes very good.

[0022] 2. The manufacturing methods of [Patent Document 1] and [Patent Document 2] were studied. As a result, it was found that only zirconium oxide could not be removed in this process. Therefore, as long as the zirconium oxide content in the silicate alkali is controlled, synthetic silica powder with a desired zirconium oxide content can be manufactured. The synthetic silica powder is made into a synthetic quartz crucible by arc discharge. By making the zirconium oxide content of the synthetic quartz crucible 10 to 50 ppm, the reactivity with barium is the same as that of natural quartz glass. Since the segregation coefficient of zirconium oxide is 1.00E-07, less zirconium oxide is mixed into the silicon single crystal. In addition, semiconductor quartz crucibles and solar cell crucibles are both multi-layered using different raw materials, but the synthetic silica powder of the present invention can be used as a whole. And the cost is comparable to that of natural quartz powder. DETAILED DESCRIPTION

[0023] The best implementation steps of the present invention are:

[0024] The results of the investigation of sodium silicate produced by the dry process showed that the zirconium oxide content was not correlated with the zirconium oxide content in the raw materials, silica sand or sodium carbonate. The zirconium oxide content in the sodium silicate was determined by the contact between zirconium oxide or zircon bricks and the sodium silicate melt in the melting furnace for producing sodium silicate flakes. The melting temperature was 1400-1500°C. In order to adjust the zirconium oxide concentration, the residence time was changed.

[0025] Sodium silicate flakes are dissolved in water in an autoclave to obtain a suspended sodium silicate aqueous solution. Diatomaceous earth is added at 80-90°C and filtered with a 0.1 μm polypropylene filter to obtain a transparent sodium silicate aqueous solution, but the zirconium oxide content in the sodium silicate is the same. However, if the zirconium oxide content of the sodium silicate flakes is made to be 50 ppm or more, the zirconium oxide content in the filtered sodium silicate will not exceed 50 ppm. Therefore, if the zirconium oxide content is 50 ppm or more, zirconium oxide particles are generated and are considered to be removed by filtration.

[0026] Therefore, the zirconium oxide content of the sodium silicate flakes should be 50 ppm or less. When the zirconium oxide content is 10 ppm or less, it has no effect on the fluorine plasma resistance, so the zirconium oxide content in the sodium silicate is 10 ppm to 50 ppm, preferably 15 to 25 ppm.

[0027] Sodium silicate is diluted with pure water to a silica concentration of 5-10%. Then, it is passed through a strongly acidic hydrogen-type cation exchange resin. This removes aluminum, iron, and most metal ions. However, since titanium is stable in divalent form, it remains in colloidal silica, so an oxidant such as hydrogen peroxide is added to make titanium peroxide, which is then passed through a strongly acidic hydrogen-type cation exchange resin again to remove it. Titanium, like silica, is not resistant to fluorine plasma, so it needs to be removed.

[0028] In order to gel colloidal silica, the hydrogen ion concentration is adjusted or heated. After freezing and thawing the gel, granular silica gel can be obtained. After the particle size is adjusted, it is boiled with dilute hydrochloric acid, returned to neutrality with ultrapure water, and calcined to become synthetic silica powder. The zirconium oxide content of the synthetic silica powder is roughly the same as that of the sodium silicate flakes. It is speculated that this is because zirconium oxide is combined with silica. Since other elements, such as metal impurities such as aluminum and titanium, exist alone, they are removed by this process if they are ionized.

[0029] Synthetic silica powder containing 10 to 50 ppm of zirconium is sintered using a device for melting natural quartz powder. This method can use hydrogen acid flame, arc melting, vacuum electric melting, continuous electric melting, plasma melting, rotary plasma melting, etc. The difference in the silanol content, the amount and size of bubbles in the melting method does not have much effect on the resistance to fluorine plasma. It is speculated that this is because zirconium oxide has a high tolerance to fluorine plasma. In the melting device of natural quartz powder, zirconium oxide bricks are mostly used as refractory materials, and some zirconium oxide is also introduced into the synthetic quartz glass by diffusion.

[0030] The evaluation method is described below. Dissolve with hydrofluoric acid and measure the purity with ICP-MS. Cut into 10mm×50mm, thickness 2mm, mirror polish, and quantify the silanol group using an infrared absorption device. Dry etch cut 30mm×30mm, thickness 2mm, grind all surfaces to a surface roughness of 0.01μm, and process the dry etching conditions at CF425sccm, Ar 125sccm, O25sccm, 80W for 1 hour. Then, calculate the etching amount based on the weight reduction. In addition, measure the surface roughness with a surface roughness meter.

[0031] Example 1

[0032] 100 kg of silica sand with an average particle size of 200 μm and 90 kg of sodium carbonate with an average particle size of 100 μm are mixed and supplied to a melting furnace with a zircon brick bed at 1400°C. Take it out after 10 hours. The sodium silicate flakes after cooling are 150 kg. The sodium silicate flakes are put into an autoclave together with 310 L of water and kept at 170-180 degrees and a pressure of about 8 kg / cm2 for 5 hours. Take out the sodium silicate aqueous solution, add 1 kg of diatomaceous earth, and filter it with a 0.1 μm polypropylene filter at 80 degrees. The molar ratio of sodium silicate is 2.4, the silicon dioxide content is 22.1%, and the total amount is 450 kg. Add 271 kg of sodium silicate and 650 kg of pure water. Pass it through a 0.1 μm polypropylene filter and pass it through 2 m3 of strongly acidic hydrogen-type cation exchange resin at SV=15. Add 300 g of 30% hydrogen peroxide water to the obtained colloidal silica and stir. 500L of strongly acidic hydrogen-type cation exchange resin was passed under the condition of SV=10. Since the hydrogen ion concentration of the obtained colloidal silica was 1.8, the hydrogen ion concentration was adjusted to 4.2 with 10% ammonium hydroxide solution. The colloidal silica gelled quickly. I put it in a refrigerator at minus 30 degrees. After 10 hours, it was confirmed that it was completely frozen and put into warm pure water at 60°C. The silica gel became granular and the water was separated from it by a centrifuge. It was dried at 200°C and kept at 90°C for 2 hours with 3% hydrochloric acid. After separating the acid with a centrifuge, it was repeatedly washed with ultrapure water until the hydrogen ion concentration was 6-7. The silica gel particles were kept at 1250°C for 5 hours. Then, it was screened with 80 mesh and 200 mesh to obtain 40kg of synthetic silica powder with 80-200 mesh.

[0033] The synthetic silica powder is sintered and transparentized by hydrogen acid flame. The hydrogen is 25m3 / H at a pressure of 2.5kg / cm3, the oxygen is 12m3 / H at a pressure of 2.5kg / H, and the supply rate of the synthetic silica powder is 2kg / H. The ingot diameter is about 200mm and the length is 500mm.

[0034] The purity of silica sand, sodium silicate crushed material, sodium silicate aqueous solution, synthetic silica powder and synthetic quartz glass in this example is shown in Example 1 of Table 1. In addition, the etching rate and surface roughness after dry etching are shown in Example 1 of Table 2.

[0035] Example 2

[0036] 100 kg of silica sand with an average particle size of 200 μm and 90 kg of sodium carbonate with an average particle size of 100 μm were mixed and supplied to a melting furnace with a zircon brick bed at 1400°C. Take it out after 15 hours. Thereafter, synthetic silica powder and synthetic quartz glass were produced under the same conditions as in Example 1. The purity of the silica sand, sodium silicate crushed material, sodium silicate aqueous solution, synthetic silica powder and synthetic quartz glass of this example is shown in Example 2 of Table 1. In addition, the etching rate and surface roughness after dry etching are shown in Example 2 of Table 2.

[0037] Example 3

[0038] 100 kg of silica sand with an average particle size of 200 μm and 90 kg of sodium carbonate with an average particle size of 100 μm were mixed and supplied to a melting furnace with a zircon brick bed at 1400°C. Take it out after 30 hours. Thereafter, synthetic silica powder and synthetic quartz glass were produced under the same conditions as in Example 1. The purity of the silica sand, sodium silicate crushed material, sodium silicate aqueous solution, synthetic silica powder and synthetic quartz glass of this example is shown in Example 3 of Table 1. In addition, the etching rate and surface roughness after dry etching are shown in Example 3 of Table 2.

[0039] Comparative Example 1

[0040] 100 kg of silica sand with an average particle size of 200 μm and 90 kg of sodium carbonate with an average particle size of 100 μm were mixed and supplied to a melting furnace with an alumina brick bed at 1400°C. The mixture was taken out after 10 hours. Thereafter, synthetic silica powder and synthetic quartz glass were prepared under the same conditions as in Example 1. The purity of silica sand, sodium silicate crushed material, sodium silicate aqueous solution, synthetic silica powder and synthetic quartz glass in this example is shown in Comparative Example 1 of Table 1. In addition, the etching rate and surface roughness after dry etching are shown in Comparative Example 1 of Table 2.

[0041] Comparative Example 2

[0042] As a comparative example, natural quartz powder was melted with acid hydrogen to produce natural quartz glass, and the dry etching characteristics were studied. The purity of natural quartz powder and the purity of natural quartz glass are shown in Comparative Example 2 of Table 1. In addition, the etching rate and surface roughness results after dry etching are shown in Comparative Example 2 of Table 2.

[0043] Comparative Example 3

[0044] As Comparative Example 3, synthetic quartz glass was produced from silicon tetrachloride by acid hydrogen flame, and its properties were studied. Comparative Example 3 in Table 1 shows the purity of natural quartz powder and the purity of natural quartz glass. In addition, Comparative Example 3 in Table 2 shows the etching rate and surface roughness results after dry etching.

[0045] Comparative Example 4

[0046] As Comparative Example 4, synthetic quartz glass was produced from silicon tetrachloride by VAD method, and its characteristics were studied. Comparative Example 4 in Table 1 shows the purity of natural quartz powder and the purity of natural quartz glass. In addition, Comparative Example 4 in Table 2 shows the etching rate and surface roughness results after dry etching.

[0047] Table 1 shows the purity of each process.

[0048] Table 1 Unit: ppm

[0049]

[0050]

[0052] Table 2 shows the characteristics after fluorine plasma treatment.

[0053] Table 2

[0054]

Claims

1. A method for producing silicon dioxide powder; characterized in that: The steps include: S1, using a zirconium-containing compound as an insulating material for a melting furnace for producing sodium silicate, and producing sodium silicate containing 10 to 50 ppm of zirconium oxide by contacting the insulating material with a sodium silicate melt; S2, heating and dissolving sodium silicate containing 10-50 ppm zirconium oxide in water under high pressure and closed environment, filtering, using hydrogen type cation exchange resin to produce colloidal silicon dioxide, gelling and sintering, to produce synthetic silicon dioxide powder containing 10-50 ppm zirconium oxide.

2. The method for producing silicon dioxide powder according to claim 1, wherein: The zirconium-containing compound is zirconium oxide or zirconium silicate.

3. The method for producing silicon dioxide powder according to claim 1, wherein: The high-pressure closed environment is achieved by an autoclave.

4. A method for producing quartz glass comprising the silicon dioxide powder according to claim 1, characterized in that: The above-mentioned silicon dioxide powder is sintered to make it transparent, thereby producing zirconium oxide-containing synthetic quartz glass.

5. A method for manufacturing a quartz crucible comprising the silicon dioxide powder according to claim 1, characterized in that: The aforementioned silicon dioxide powder is melted by arc discharge to prepare a synthetic quartz crucible containing zirconium oxide.